Educational Advocacy for Child Victims of Sexual Violence in the Special Region of Yogyakarta - Donda Sihite (Spektrum Analisis Kebijakan Pendidikan, 2025)
The objectives of this research to describe the process of educational advocacy for child victims of sexual violence by the Pusat Pelayanan Terpadu Perempuan dan Anak Korban Kekerasan “Rekso Dyah Utami” (P2TPAKK “RDU”) and its network, the characteristics of sexual violence cases in children, and a solution assistance scheme for child victims of sexual violence to prevent the recurrence of cases of violence. This research uses a descriptive qualitative approach, where sexual violence against children is analyzed with the study of educational advocacy in the perspective of Paulo Freire's “Conscientizacao” theory. Data collection was done by interviews, documentation, and analysis of archival recordings. The results of this study are the process of educational advocacy for child victims of sexual violence carried out by P2TPAKK “Rekso Dyah Utami” by networking in the Forum for the Forum Perlindungan Korban Kekerasan (FPKK). Consciousness transformation as a long-term goal of educational advocacy has not been a priority in handling cases in shelter. P2TPAKK “RDU” prioritizes changing the attitudes and hearts of victims through the integration of preventive, curative, and rehabilitative stages in the prevention and handling of sexual violence in children.